2022
DOI: 10.1186/s12863-021-01021-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of genetic variation on gene regulation in cancer in the context of 3D genome structure

Abstract: Background Numerous genome-wide association studies (GWAS) conducted to date revealed genetic variants associated with various diseases, including breast and prostate cancers. Despite the availability of these large-scale data, relatively few variants have been functionally characterized, mainly because the majority of single-nucleotide polymorphisms (SNPs) map to the non-coding regions of the human genome. The functional characterization of these non-coding variants and the identification of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 140 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…Nonetheless, we found that only a few specific genetic variations (such as in enhancer regions) associated with allelic PEI rewiring likely contribute to differences in SMT physiology and phenotype between the specialized broiler (meat‐producing) and layer (egg‐producing) chickens. In contrast to the large chromosome rearrangements leading to cancers [ 51 ] or severe developmental disorders [ 52 ] through dramatic 3D genome reorganizations (e.g., TAD shifts), most breed‐specific variations, although probably causing allelic PEI rewiring, had a subtle phenotypic effect. We speculate that this is most likely due to remarkable redundancy in contacts among rewired enhancers carrying high‐ F ST variants (Figure 6C–E ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, we found that only a few specific genetic variations (such as in enhancer regions) associated with allelic PEI rewiring likely contribute to differences in SMT physiology and phenotype between the specialized broiler (meat‐producing) and layer (egg‐producing) chickens. In contrast to the large chromosome rearrangements leading to cancers [ 51 ] or severe developmental disorders [ 52 ] through dramatic 3D genome reorganizations (e.g., TAD shifts), most breed‐specific variations, although probably causing allelic PEI rewiring, had a subtle phenotypic effect. We speculate that this is most likely due to remarkable redundancy in contacts among rewired enhancers carrying high‐ F ST variants (Figure 6C–E ).…”
Section: Discussionmentioning
confidence: 99%
“…interacting regions led to the upregulation of target genes 58,64 . It is also conceivable that disruption of the mechanisms underlying this threedimensional chromatin conformation by disease-associated SNPs may affect such physical interactions and lead to disrupted gene expression and disease [137][138][139] . MPRAs that simultaneously screen diseaseassociated SNPs for their effect on potential regulatory activity have been performed [140][141][142][143] .…”
Section: Silencers As Therapeutic Targetsmentioning
confidence: 99%
“…Colon cancer and rectal cancer are often grouped together known as CRC because these two cancers share many similar features, including symptoms, risk factors, and basic cell biology. Because cancer is a condition of genetic variations, 1 , 2 where the mutations can cause genes to function abnormally and result in alternative expression. Proteins, which are final products of gene expression, have influence on phenotypes and various biological processes.…”
Section: Introductionmentioning
confidence: 99%